Limitations of Contract Farming as a Pro-poor Strategy: The Case of Maize Outgrower Schemes in Upper West Ghana. (February 2018) - Ragasa, Catherine; Lambrecht, Isabel; Kufoalor, Doreen S.
Highlights: Participation in maize contract farming (CF) in a remote region in Ghana led to improved technology adoption and yields. However, on average, yields were not high enough to compensate for higher input costs. Impact of CF on profits was negative even after accounting for input diversion from CF schemes. Scheme participation and profits from CF schemes are linked to wealth indicators. Without technology improvements, maize CF is limited as a broad-based pro-poor development strategy in Ghana. Summary: Contract farming (CF) arrangements have the potential to address market failures and improve technology adoption, productivity, and welfare. In Ghana, government and donors use CF as a strategy for increasing adoption of new agricultural technologies and developing value chains. Yet to date, there has not been a rigorous assessment of these CF schemes. The focus in this paper is on different maize-based CF schemes in the poorest and most remote region in Ghana. It assesses the profitability and potential impact of these CF schemes, utilizing a unique plot-level dataset that covers two periods of data and two maize plots (scheme and non-scheme) per household, and employing matching techniques and an instrumental variable approach to address selection bias and unobserved heterogeneity across farmers. These are complemented by a community-level survey, in-depth interviews with scheme operators, and a series of key informant interviews. Results show that these schemes led to improved technology adoption and yield increases. In addition, a subset of maize farmers with high yield improvements due to CF participation have high profits. Maize CF schemes also enabled market coordination and consistent supply of quality maize to downstream industries. However, on average, the impact of the CF schemes on profitability is negative, even when input diversion is accounted for. Yield increases are not high enough to compensate for higher input requirements and the cost of capital under the schemes. Despite higher yields, the costs to produce one metric tonne of maize under CF schemes are higher than on maize farms without CF schemes, twice that of several countries in Africa, and more than seven times higher than that of major maize-exporting countries (the United States, Brazil, and Argentina). Sustainability of these CF schemes will largely depend on developing and promoting much-improved varieties and technologies that boost yields in order to compensate for the high input and credit costs.